En studie kring välfärdsindikatorer i mjölkproduktionen - Strandberg, Sofia (2009)
In this final thesis a study about welfare indicators in the Swedish milk production has been carried out. The system Swedish Animal Welfare Monitoring Scheme developed by the Swedish Dairy Association has been used as a base and the EU project WELFARE QUALITY® has also been used as a source of information. Focus groups have been used as a qualitative investigating method. This included four focus groups, two with farm auditors from the two different dairies and two with dairy farmers. This method was chosen because in this way one can study how a conversation about a given subject takes form in a respectable way. You can also gain knowledge about people's experience and understand the underlying reasons behind the opinions. A literature study about welfare indicators in milk production, a study about the IP SIGILL certification system, and the trade organization Swedish Dairy Association have been carried out as a background and base to the qualitative studies.